PANDANGAN UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN TERHADAP PERJANJIAN BAKU - Abdul Latif (Jurnal Ilmiah Cano Ekonomos, 2016)
Standard contract is an agreement whose contents are made by one party only, whileothers do not have the opportunity to negotiate or ask for a change to the contents. Thepurpose of this study is to see the validity of the standard contract when viewed from theperspective of Law No. 8 of 1999 on Consumer Protection . This study uses normativejuridical method , using data sources , such as primary legal materials , secondary legalmaterials , and tertiary legal materials . Then the data obtained was done using descriptivemethod of analysis . Results of this research is that in the view of the Law No. 8 of 1999 onConsumer Protection , the raw agreement is not prohibited along the raw contents of theagreement does not contain terms that contain conditions restricting or removing entirelythe responsibility borne by the employer